Academic excellence as a determinant of self-confidence among graduates of ODL programs. Issue 3 (30th October 2020) - Sembiring, Maximus Gorky
Abstract : Purpose: This study envisioned plausible influential factors on service quality and academic excellence relatable to graduate self-confidence in an open distance learning (ODL) outlook. The objective was to expose the moderating role of academic excellence (graduate satisfaction) between service quality and self-confidence (engagement, achievement, loyalty and opportunity, EALO). It was also of interest to explore how, in what routines factors involved interrelated. Design/methodology/approach: This study utilized exploratory design. Qualitatively, service quality included acclimation, advising, module, tutorial, assessment, feedback and referral factors. Service quality led to academic excellence (GPA, study length, relevance and recognition). Besides, academic excellence influenced self-confidence. Quantitatively, service quality, academic excellence and self-confidence were the independent, moderating and dependent variables. Respondents were randomly selected through a survey of eligible Universitas Terbuka alumni. Findings: 11 hypotheses were assessed under structural-equation modeling (SEM). Responses from 122 out of 500 graduates were completed. Eight hypotheses were validated by the analysis. The tutorial was the most influential factor followed by module, assessment and acclimation; advising, feedback and referral were excluded. Academic excellence also led to self-confidence. The study was able to visualize a substantial role of academic excellence in moderating service quality to EALO. Besides, important-performance analysis and customer-satisfaction index (IPA-CSI) recognized 21 out of 32 attributes as the pillars of academic excellence. Originality/value: Three of the hypotheses were invalidated by the quantitative analysis. Further inquiry with much broader coverage is then required to diminish the variance to finally find the ideal framework.